IMPLEMENTASI PENANAMAN KESADARAN PENTINGNYA KETERAMPILAN SOFT SKILLS ENTREPRENEURSHIP WADAH PENGEMBANGAN FKIP UNBARI - Harbeng Masni; Ade Rahima; Zuhri Saputra Hutabarat (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2021)
Implementation of Instilling Awareness of the Importance of Soft Skills Entrepreneurship Through Student Development FKIP UNBARI "is aimed at providing an experience for students to care about cooperative development. Schools are expected to be a means for students to learn to do small businesses, develop organizational skills, encourage habits to innovate, learn to complete and as a forum for students to face the world of work after graduating from school. This research was conducted on FKIP UNBARI students. School cooperatives can provide an experience for students to care about the development of cooperatives. School cooperatives are expected to be a means for students to learn to do small businesses, develop organizational skills, encourage habits to innovate, learn to solve problems and so on.Keyword: Entrepreneurship Soft Skills